An outline of the problem of employing athletes by sport clubs in Poland - Daria Pałucka (Kazimierz Wielki University, 2017)
The purpose of this article is to outline the problem of employing athletes by sports clubs in Poland. For the conditions of employment of athletes, the legal form under which the work is performed is very important. In addition, the internal organization rules of sport associations play a vital role in influencing the content of professional contracts. The article attempts to present the characteristics of hiring employees in the employee and non-employee form.